The Worship Of Durgā In Bali (A Brief History, Perceptions And Places Of Worship Of The Goddess Durgā In Bali) - Si Luh Nyoman Seriadi; Marsono (Jayapangus Press, 2020)
Durgā is one of the objects of worship in Bali since ancient times. The evidence is strengthened by discovering traces of worship, several statues, and other artifacts. This research describes the worship of Durgā in Bali, the community's perceptions, and places of worship of Durgā in Bali. The results showed different perceptions and distortions of worshiping Durgā in Bali, which was associated with worshiping Sakti in the aspect of negative power (black magic). This is related to various mythologies that have developed in Bali, which influence people's beliefs.